PENENTUAN PROFIL ELUSI IODIUM-125 SEBAGAI PERUNUT UNTUK TUJUAN RADIOIMMUNIASSAY (RIA) - Maiyesni Maiyesni; Mujinah Mujinah; Dede Kurniasih; Witarti Witarti; Triyatno Triyatno; Herlan S (Jurnal Sains dan Teknologi Nuklir Indonesia (Indonesian Journal of Nuclear Science and Technology), 2016)
Manfaat iodium-125 (125-I) sudah banyak diketahui. 125-I  dapat digunakan antara lain sebagai perunut dalam teknik Radioimmunoassay (RIA) untuk deteksi dini berbagai penyakit kanker, menentukan kesuburan hewan ternak serta cemaran mikotoksin di dalam pangan secara invitro.  125-I  yang dibutuhkan dalam teknik ini disamping harus mempunyai kemurnian radiokimia > 95%,  konsentrasi radioaktifitas   juga tinggi, sehingga volume  125-I  haruslah sekecil mungkin. Dengan demikian perlu dipelajari profil elusi 125-I dari kolom reduktor Jones saat proses peningkatan kemurnian  radiokimia. Penelitian ini bertujuan untuk menentukan volume optimal  eluat dengan efisiensi dan kemurnian radiokimia yang dapat diterima. Pada penelitian ini kondisi kolom yang dipilih adalah kolom dengan pH basa. Kolom reduktor Jones yang mengandung  125-I dielusi dengan larutan  NaOH 0,01N secara  fraksinasi volume 1 ml. Radioaktifitas  masing-masing fraksi diukur menggunakan  dose calibrator. Penentuan kemurnian radiokimia dilakukan pada fraksi yang memiliki radioaktifitas  tertinggi dan fraksi gabungan  dengan  metode kromatografi kertas. Radioaktifitas  tertinggi ditunjukkan pada  fraksi kedua  yaitu  16,59  mCi dengan efisiensi 33,95% dan fraksi gabungan yaitu 50,19 mCi dengan efisiensi 92,26%. Kemurnian radiokimia 125-I bulk, fraksi kedua dan fraksi gabungan berturut-turut adalah 41,50, 97,5  dan  98,50%.  Volume optimal eluat adalah 7 ml serta  pH 125-I sebelum dan sesudah fraksinasi adalah 10 -11.  Determination of  Elution Profile the Iodine-125 as a tracer for Radioimmunoassay (RIA). The benefits of the Iodine-125 (125I ) isotope was well known. 125I are used as radiotracer in Radioimmunoassay (RIA) technique for early detection of cancer, determine of hormone content which related with fertility of livestock and also for contamination detection of mycotoxins on food by in vitro.  125I which is needed in this technique not only must have high radiochemical purity above 95% but also high radioactivity concentration, so that  125I volume which is use must as little as possible. Therefore, 125I elution profile for increasing radiochemical purity using a reductor Jones column should be studied. Aim of this study is to determine the optimum volume of eluate which have efficiency and radiochemical purity that can be accepted. The preliminary study was conducted to determine the optimal conditions of reductor Jones  column. Reductor Jones column is conditioned on neutral and alkaline pH. At this elution study, the columns conditions selected is alkaline pH. Reductor Jones column which containing 125I eluted with NaOH 0,01 N solution by fractionated in 1mL. The radioactivity of each fraction is measured with dose calibrator.  Determination of the radiochemical purity of carried out on the fraction which have the highest radioactivity and the combined fractions using paper chromatography. Highest radioactivity is shown in the second fraction at 16,59 mCi with efficiency 33,95%  and combined fractions at 50,19 mCi with efficiency 92,26%. The radiochemical purity of 125-I bulk, second fraction and combined fractions are 41,50%, 97,5 % dan  98,50%, respectively.  Optimum fraction is 7 mL and pH of 125-I before and after fractination are 10-11. By studying the elution profile can be known that the optimal volume is the smallest total volume of eluent with efficiency and radiochemical purity level that can be accepted.